2004
DOI: 10.1002/jmv.20093
|View full text |Cite
|
Sign up to set email alerts
|

Early inhibition of nitric oxide production increases HSV‐1 intranasal infection

Abstract: Here, we studied the role of nitric oxide (NO) production during the first steps of the respiratory infection of BALB/c mice with herpes simplex virus type 1 (HSV-1), strain F. Nitric oxide synthase II (NOS-II) mRNA and protein were detected by reverse transcription (RT)-PCR and dot blot, respectively in samples of lungs and turbinates early post-infection (p.i.). Immunohistochemical analysis revealed pulmonar macrophages and PMN expressing NOS-II in the lungs of infected animals. Animals intranasally treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 67 publications
(66 reference statements)
2
19
0
Order By: Relevance
“…IL-12, in synergy with IFN-α/β, can enhance the production of IFN-γ by NK cells (Hunter et al, 1997). IFN-γ released by NK cells subsequently activates macrophages to produce inducible nitric oxide synthase (iNOS), which produces NO to limit HSV replication (Croen, 1993; Gamba et al, 2004). …”
Section: Immune Control Of Primary Corneal Infectionmentioning
confidence: 99%
“…IL-12, in synergy with IFN-α/β, can enhance the production of IFN-γ by NK cells (Hunter et al, 1997). IFN-γ released by NK cells subsequently activates macrophages to produce inducible nitric oxide synthase (iNOS), which produces NO to limit HSV replication (Croen, 1993; Gamba et al, 2004). …”
Section: Immune Control Of Primary Corneal Infectionmentioning
confidence: 99%
“…NO is a product of the cellular immune system that is well known as a reactive free radical molecule that modulates cytokine expression, and it is beneficial to the host defense against virus infections (61). For example, cells with iNOS inhibited by 1-NG-monomethyl arginine (1-NMMA) failed to restrict Japanese encephalitis virus (JEV) replication (62), and IFN-␥-induced iNOS and NO production inhibited the replication of vaccinia virus (VV) and HSV-1 (17,63). Our observations implicating NO in resistance to HIV-1 are consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Early inhibition of NO by i.n. administration of aminoguanidine (AG) was found to increase HSV-1 infection in the eyes and lungs of mice (17). Conversely, pretreatment with an NO donor, sodium nitroprusside (SNP), decreased the titer of Sindbis virus (18).…”
mentioning
confidence: 99%
“…On the one hand, Fujii et al [13] reported that inhibition of NOS by the nonselective NOS inhibitor L -NG-monomethyl arginine citrate several days after nasal inoculation of HSV-1 led to a significant amelioration of encephalitis, suggesting that high levels of NO produced by iNOS are a pathogenic factor in HSV-1 encephalitis. On the other hand, Gamba et al [17] showed that early administration of the selective iNOS inhibitor facilitated HSV-1 infection and increased the inflammatory process. In accordance with the latter finding, our results may suggest that the reduction in cNOS activity in the brain during the early stages of the viral infection could be one mechanism that facilitates HSV-1 infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that NOS activity may be involved in the early stages of the viral infection. It should be noted that in all previous reports, only the response of iNOS to HSV-1 was examined [13,14,16,17] . In view of the above, we were interested in examining both iNOS and constitutive NOS (cNOS) activity in different parts of the brain and in cultured glial cells during the early stages of HSV-1 infection.…”
mentioning
confidence: 99%